ANALISA PUTUSAN BANDING BERKAITAN DENGAN EKUALISASI PAJAK PENGHASILAN DAN PAJAK PERTAMBAHAN NILAI - Angelia Angelia; Retnaningtyas Widuri (Tax & Accounting Review, 2014)
This research was conducted to know the scheme of The Appeal Decision from Tax Court concerning with the Tax Base of Value Added Tax that related with The Equalization of Income Tax and Value Added Tax. This research analyzing 15 decisions taken from the tax year of 2007-2009. From the 15 decisions, The Council decided to accept entirely 7 disputes, 6 disputes was accepted partially, and 2 disputes rejected. The motive of this 15 decisions was the difference in sales reporting on Corporate Income Tax Return, Value Added Tax Return, and the corrections in the Corporate Income Tax that also set for the correction of Tax Base of Value Added Tax. In the trial, the evidence that often used was the written evidence and the recognition of the disputed parties. If it was in accordance with The Council, the evidence submitted by the appellant was strong and appropriate with the provisions of taxation so The Appeal would be accepted and the correction that The Appellee set was canceled, but if the evidence that submitted by The Appellee was strong and appropriate with the provisions of taxation so the correction will be maintained and The Appeal would be rejected. If there was correction that was maintained and was not maintained in a dispute, so the dispute was decided to be accepted in partially by The Council.